PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS BUDAYA LOKAL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SMA NEGERI 3 PADANG - Rani Rahim; Nur Rahmi Rizqi; Sartika Wati (Universitas Dharmawangsa, 2026)
The purpose of this study is to develop a valid, practical, and effective Minangkabau local culture-based Student Worksheet (LKPD) to improve students' mathematical communication skills at SMA Negeri 3 Padang. This study uses the Research and Development (R&D) method with the ADDIE development model. The subjects of this study were 32 grade X students of SMA Negeri 3 Padang. Observation sheets, practicality questionnaires, mathematical communication ability tests, and validation sheets were the research instruments. The results showed that the developed LKPD met the valid criteria with an average validation score of 3.65 which is a very valid category, practical with an average practicality score of 3.72 which is a very practical category, and effective with an average N-gain score of 0.74 which is a high category. This LKPD integrates the context of Minangkabau local culture such as the traditional house, songket weaving, and rendang in mathematical materials, especially geometry and linear equation systems. This study concludes that local culture-based LKPD can be an effective alternative teaching material to improve students' mathematical communication skills.